Use of API in Data Warehouse Integration for One Data Stunting Presentation - Arik Sofan Tohir; Bambang Wiseno; Zulvana Zulvana (Generation Journal, 2026)
The Office of Population Control, Family Planning, Empowerment of Women and Child Protection (DP2KBP3A) of Kediri Regency is one of the key government agencies responsible for stunting management. To monitor the current status of stunting in the region, DP2KBP3A utilizes the 'Aksipenting' application (Stunting Monitoring Integration Application), a platform designed for stunting data entry across Kediri Regency. Beyond stunting monitoring, Aksipenting is also employed to track the health conditions of prospective brides, pregnant women, and postpartum mothers. The system processes data across three hierarchical levels: the cadre level, the district level, and the regency level. While DP2KBP3A manages comprehensive stunting data through this application, data integration across Regional Government Agencies (OPD) continues to face challenges regarding standarization and interoperability. This study aims to design and implement a Data Warehouse-based Application Programming Interface (API) to support the 'One Data Stunting' policy across various agencies. The system development follows a Research and Development (R&D) approach using the Rapid Application Development (RAD) method to produce a reliable, standarized, and accessible data integration solution as a foundation for decision-making in accelerating stunting reduction